Edukasi Pemanfaatan Rimpang Kunyit untuk Meningkatkan Imunitas Tubuh di Pandemi COVID-19 - Syafira Az Zahro; Agustin Wulan Suci Dharmayanti; Dwi Warna Aju Fatmawati; Lusi Hidayati (Dental Agromedis, 2024)
In 2019, a new type of corona virus (SARS-CoV-2) has spread, whose disease is called Coronavirus disease 2019 (COVID-19). This virus was discovered in Wuhan, China for the first time and has infected 90,308 people as of March 2, 2020. The number of deaths has reached 3,087 people or 6%, the number of patients who have recovered is 45,726 people. Common symptoms include fever, cough and difficulty breathing. Until the beginning of 2021, Covid 19 was still a pandemic that occurred in Indonesia. One year on, there are still many people who do not understand how to properly implement the COVID 19 protocol. Indonesia is among the top 25 countries in the world with the highest number of positive cases of coronavirus disease (Covid-19). East Java is one of the provinces in Indonesia which accounts for the most positive cases of corona. The number of confirmed positive patients in East Java continues to increase due to the lack of public awareness in implementing health protocols as an effort to prevent transmission of the coronavirus. In times of apandemic it is not known when it will end, anticipation such as strengthening immunity also needs to be done. The curcumin found in the turmeric plant can be used as a drink to increase immunity. Besides being easy to find, turmeric also has a cheap price. The identical taste of herbal medicine that some people don't like causes people to think that increasing body immunity in the midst of the COVID -19 pandemic will be less effective. So that a tea extract from turmeric is made that is easy for the community to practice on a daily basis. The method used is direct education. The education was carried out to help the community by distributing information about the COVID-19 health protocol and also increasing immunity to prevent exposure to COVID-19.Keywords: COVID-19; Curcumin; Housewife.